STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI MISKONSEPSI AGAMA DIKALANGAN SISWA SMP NEGERI 4 METRO - yuleha wulandari; prabowo; noormawanti (PROFETIK: Jurnal Mahasiswa Pendidikan Agama Islam, 2026)
Religious misconceptions experienced by students at SMP Negeri 4 Metro lead to misunderstandings of religious teachings and impact their attitudes and behavior. The purpose of this study was to identify the causes of religious misconceptions, determine teachers' strategies for addressing them, and explore supporting and inhibiting factors in addressing religious misconceptions among students. This study used a qualitative approach with historical studies methods to analyze past events and understand their impact on the current situation. Data were collected through in-depth interviews, observation, and documentation, and then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that religious misconceptions among students at SMP Negeri 4 Metro are caused by misunderstandings in religious teachings. To address this problem, strengthening basic religious understanding and building positive interpersonal relationships is necessary. Strategies implemented by teachers include accustoming students to complying with religious norms, instilling tolerance, and practicing religious moderation. These steps aim to protect students from negative influences and deviant teachings. Supporting factors include fostering tolerance and school support, as well as inhibiting factors, namely, the time it takes to change habits. Despite these obstacles, the school strives to address the problem through regular evaluations.